BEYOND CERTIFICATION: RECONCEPTUALIZING MUSLIM CONSUMER TRUST IN THE HALAL ECONOMY THROUGH RELIGIOSITY, DIGITAL ENGAGEMENT, AND ETHICAL GOVERNANCE - Syaeful Bahri; Alfisah; Sukemi; Subroto; Ade Adhariah (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines the evolving dimensions of Muslim consumer trust in halal-certified cosmetic products within the context of Islamic economic principles, particularly maqāṣid al-sharī‘ah and ethical consumption in the digital era. This study employs a narrative literature review through thematic synthesis of forty-five peer-reviewed articles published between 2018 and 2025. Relevant studies were systematically selected from major academic databases to identify the key determinants shaping Muslim consumer trust. The findings reveal four interconnected dimensions influencing trust formation: religiosity and spiritual identity, halal certification and perceived authenticity, digital engagement and electronic word-of-mouth (e-WOM), and eco-consciousness as an extension of the halālan ṭayyiban principle. The study demonstrates that halal trust is no longer shaped solely by certification, but increasingly reinforced through digital interaction, ethical awareness, institutional transparency, and perceived integrity. Halal certification also functions as an institutional governance mechanism that strengthens trust across the broader halal economic ecosystem, including Islamic finance. This study is limited by its reliance on secondary data and narrative synthesis, which may reduce contextual generalizability across different regions and industries. This study proposes an integrative conceptual framework linking religiosity, digital engagement, ethical governance, and halal trust formation within Islamic economics, offering insights for strengthening sustainable and trust-based halal governance systems.